UJI BEBERAPA KONSENTRASI PUPUK CAIR Azolla pinnata PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN AWAL - Prami Astuti; Sampoerno '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research about Test Of Some Azolla pinnata Liquid Fertilizer Concentration On The Growth Of Oil Palm Seeds (Elaeis guineensis Jacq.) In Pre Nursery has been done in the experimental garden of Agriculture’s Faculty, University of Riau. This study aimed to determine the effect of Azolla pinnata liquid fertilizer and get the best concentration for the growth of oil palm seeds in the pre nursery. This Research was caried out experiments using a Completely Randomized Design (CRD), which consists of 5 treatments and 4 replications, the treatments were A1: Azolla liquid fertilizer concentration 50 g/l, A2: Azolla liquid fertilizer concentration 75 g/l, A3: Azolla liquid fertilizer concentration 100 g/l, A4: Azolla liquid fertilizer concentration 125 g/l, A5: Azolla liquid fertilizer concentration of 150 g/l. The results show the Azolla liquid  fertilizer significantly effected on plant height, number of leave, stem diameter  and dry weight of plant, but not significantly effected root crown ratio. Azolla liquid fertilizer application at a concentration of 100 g/l and 125 g/l gives the best result and increasing the growth of oil palm seeds in pre nursery.   Keywords: Azolla liquid fertilizer, oil palm, pre nursery